Mycobacteria in Minas cheese commercialized in open fairs in São Paulo, Brazil - Patricia Rossi Moriconi; Cássia Yumi Ikuta; Fábio Gregori; Gisele de Oliveira; Sheila de Oliveira; Paloma de Oliveira Tonietti; José Soares Ferreira Neto; Fernando Ferreira; Adriana Cortez; Evelise Oliveira Telles (Brazilian Journal of Veterinary Research and Animal Science, 2018)
Mycobacterium bovis is the causative agent of bovine tuberculosis, a disease that affects dairy herds throughout the Brazilian territory, constituting a neglected zoonosis transmitted by raw milk and its derivatives. In this study, we evaluated the presence of M. bovis and other mycobacteria in Minas cheese obtained from open fairs in the city of São Paulo between 2012 and 2013. Samples (n = 133) were decontaminated using hexa-cetylpyridinium chloride and seeded on Stonebrink–Leslie medium. The isolates were submitted to molecular identification by TB Multiplex PCR targeting the 16S rRNA gene and amplicon nucleotide sequencing. From 16 cheese samples (12%), we obtained 26 putative colonies of Mycobacterium spp., none of which belonged to any of the Mycobacterium tuberculosis, Mycobacterium avium, or Mycobacterium intracellulare complexes. Phylogenetic analysis showed that sample sequences were grouped in a clade that includes only non-tuberculous mycobacteria with proximity to sequences obtained from Mycobacterium novocastrense (3 sequences), Mycobacterium holsaticum (1 sequence), and Mycobacterium elephantis (2 sequences). Although no epidemiological evidence was found regarding the importance of oral transmission of mycobacteria in healthy people, their importance in the immunosuppressed population remains uncertain.